Introgressive hybridization as a promoter of genome reshuffling in natural homoploid fish hybrids (Cyprinidae, Leuciscinae) - Pereira, C S A; Aboim, M A; Ráb, P; Collares-Pereira, M J (Heredity, 2014)
Understanding the mechanisms underlying diversification and speciation by introgressive hybridization is currently one of the major challenges in evolutionary biology. Here, the analysis of hybridization between two pairs of Iberian Leuciscinae provided new data on independent hybrid zones involving Achondrostoma oligolepis (AOL) and Pseudochondrostoma duriense (PDU), and confirmed the occurrence of hybrids between AOL and Pseudochondrostoma polylepis (PPO). A multilevel survey combining morphological, genetic and cytogenomic markers on a vast population screening successfully sorted the selected fishes as admixed. Results were similar in both AOL × PDU and AOL × PPO systems. Overall, hybrid morphotypes, cytogenomic data and genetic profiling indicated preferential backcrossing and suggested AOL as a major genomic contributor. Moreover, results implied AOL as more permissive to introgression than PDU or PPO. Although PDU- and PPO-like individuals appeared more resilient to genome modifications, AOL appeared to be more involved and affected by the ongoing hybridization events, as chromosomal translocations were only found in AOL-like individuals. All hybrids analysed evidenced extensive ribosomal DNA (rDNA) polymorphism that was not found in parental species, but usually seen falling within the range of possible parental combinations. Yet, transgressive phenotypes that cannot be explained by normal recombination, including more rDNA clusters than expected or the occurrence of syntenic rDNAs, were also detected. Present results proved rapid genomic evolution providing the genetic novelty for species to persist. In addition, although the ultimate consequences of such apparently extensive and recurrent events remain unknown, modern genome-wide methodologies are of great promise towards answering questions concerning the causes, dynamics and impacts of hybridization.
Keywords: Portugalsko; karyotyp; populační genetika; DNA, Ribosomal; Hybridization, Genetic; telomery; Synteny; Genetics, Population; Female; genom; Genome; syntenie; zvířata; hybridizace genetická; Telomere; ženské pohlaví; Karyotype; Male; Chimera; ribozomální DNA; Animals; mužské pohlaví; Portugal; chiméra; Cyprinidae